Synthesis, Structural Properties and Biocidal Studies of 3d-Transition Metal Complexes with Diphenylamine Compounds and Schiff Bases - Tomar, Sapna; Sharma, R.C. (Asian Journal of Chemistry, 2016)
A number of new mixed ligand complexes of Co(II), Ni(II), Cu(II) and Zn(II) containing diphenylamine-2-hydroxy-2-carboxylic acid (DPHC) and furfuralidine-2-amino thiazole (FAT) have been synthesized and characterized by elemental analysis, TLC, conductivity measurements and IR spectral data.